Assessing the influence of consumer education, personality and social media in halal purchase behavior - Muhammad, Muhammad Arif; Abu Bakar, Elistina; Muhammad Arif, Afida Mastura; Ahmad, Sa'odah; Md Jusoh, Zuroni (ANSI Network, 2019)
Background and Objective: Recognizing the importance of halal to Muslim consumers had caused the traders to use the concept of halal as a form of marketing. However, Muslim consumers often face problems to ensure that the products they buy, including cosmetics are truly halal as they can only rely on the certification of the authorities. Rather than looking from a marketing perspective, this study was an exploration from consumer empowerment aspects. The objective of the study was to predict the determining factors that influence consumer behavior when buying halal food products. The study focused on four factors which were the intensity of consumer education, the personality of assertiveness and aggressiveness and the role of social media. Materials and Methods: This study was conducted in Malaysia and the data collection was done between December 2017 to March 2018. A total of 400 Muslim respondents participated in this study and were chosen through stratified random sampling. Multiple linear regressions were used to identify the factors that contributed to consumer behavior. Results: Results showed that only the intensity of consumer education and the personality trait of assertiveness were able to explain a 7.1% variance in the behavior of the respondents while buying halal food products. The results also found that the personality of aggressiveness and social media were not the predictive factors of consumer behavior. The most influential variable was the intensity of consumer education. Conclusion: This research holds significant implications for the government and consumer associations, to give emphasis to effective consumer education programs to inculcate good purchase behavior among consumers.